2021
DOI: 10.1186/s12893-021-01241-z
|View full text |Cite
|
Sign up to set email alerts
|

Rescue radiofrequency ablation or percutaneous ethanol injection: a strategy for failed RALPPS stage-1 in patients with cirrhosis-related hepatocellular carcinoma

Abstract: Background The future liver remnant (FLR) faces a risk of poor growth in patients with cirrhosis-related hepatocellular carcinoma (HCC) after stage-1 radiofrequency-assisted ALPPS (RALPPS). The present study presents a strategy to trigger further FLR growth using supplementary radiofrequency ablation (RFA) and percutaneous ethanol injection (PEI). Methods At RALPPS stage-1 the portal vein branch was ligated, followed by intraoperative RFA creating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A 2022 study of 107 patients with large HCC lesions found that transarterial ethanol ablation (TEA) had significantly better tumor response and OS, with the average OS being 21.6 months compared with 9.9 months for historical cohort of TACE and TARE. [24][25][26] Tumor size has been found to be very significant in response to PEI with the best responses for lesions < 5 cm, ideally <3 cm. 27,28 For those patients who are candidates for PEI, a 2020 study demonstrated success in further modulating the localization of the ethanol injection with the use of ethyl cellulose (EC).…”
Section: Trial Outcomesmentioning
confidence: 99%
“…A 2022 study of 107 patients with large HCC lesions found that transarterial ethanol ablation (TEA) had significantly better tumor response and OS, with the average OS being 21.6 months compared with 9.9 months for historical cohort of TACE and TARE. [24][25][26] Tumor size has been found to be very significant in response to PEI with the best responses for lesions < 5 cm, ideally <3 cm. 27,28 For those patients who are candidates for PEI, a 2020 study demonstrated success in further modulating the localization of the ethanol injection with the use of ethyl cellulose (EC).…”
Section: Trial Outcomesmentioning
confidence: 99%
“…Surgical hepatectomy, percutaneous ethanol injection, percutaneous radiofrequency ablation and hepatic artery chemoembolization are the primary treatment modalities for relatively small HCC tumors, but not diffuse or multiple tumors, and the liver has sufficient reserve capacity. [23][24][25] However, patients with multiple, large tumors or metastases are eligible for systemic chemotherapy. 26 In conventional chemotherapy, hepatocytes detoxify the drug, which reduces the drug efficiency for HCC.…”
Section: Introductionmentioning
confidence: 99%